Proof‐of‐concept evidence for trimodal simultaneous investigation of human brain function. Issue 13 (23rd June 2021) - Moore, Matthew; Maclin, Edward L.; Iordan, Alexandru D.; Katsumi, Yuta; Larsen, Ryan J.; Bagshaw, Andrew P.; Mayhew, Stephen; Shafer, Andrea T.; Sutton, Bradley P.; Fabiani, Monica; Gratton, Gabriele; Dolcos, Florin
Abstract: The link between spatial ( where ) and temporal ( when ) aspects of the neural correlates of most psychological phenomena is not clear. Elucidation of this relation, which is crucial to fully understand human brain function, requires integration across multiple brain imaging modalities and cognitive tasks that reliably modulate the engagement of the brain systems of interest. By overcoming the methodological challenges posed by simultaneous recordings, the present report provides proof‐of‐concept evidence for a novel approach using three complementary imaging modalities: functional magnetic resonance imaging (fMRI), event‐related potentials (ERPs), and event‐related optical signals (EROS). Using the emotional oddball task, a paradigm that taps into both cognitive and affective aspects of processing, we show the feasibility of capturing converging and complementary measures of brain function that are not currently attainable using traditional unimodal or other multimodal approaches. This opens up unprecedented possibilities to clarify spatiotemporal integration of brain function. Abstract : By overcoming the methodological challenges posed by simultaneous recordings, the present report provides proof‐of‐concept evidence for a novel approach using three complementary imaging modalities: functional magnetic resonance imaging, event‐related potentials, and event‐related optical signals. Using the emotional oddball task, a paradigm that taps into both cognitive and affective aspects of processing, we show the feasibility of capturing converging and complementary measures of brain function that are not currently attainable using traditional unimodal or other multimodal approaches. This opens up unprecedented possibilities to clarify spatiotemporal integration of brain function.